Hubungan Karakteristik Individu dengan Perilaku SADARI pada Mahasiswi di Masa Pandemi COVID-19 - Hoirun Nisa; Serly Marliana; Tri Murti; Nurunnisa Azzahra (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2022)
Breast cancer remains the leading cause of death for women globally. In Indonesia, breast cancer is the most prevalent cancer and the incidence continuous to increase. Breast self examination (BSE) is considered the most practical preventive measure for breast cancer with many advantages. The purpose of this study was to determine the factors associated with BSE behavior among university students of UIN Syarif Hidayatullah Jakarta during the pandemic COVID-19. The study was conducted using cross-sectional design. The number of respondents were 354 female students, selected using purposive sampling. Data were analyzed using chi-square test for categorical variables and t-test for continuous variables. A total of 57% respondents performed BSE. There was a relationship between age and BSE behavior (p=0.006), while BMI, age at menarche, level of knowledge, attitudes, and family history were not associated with BSE behavior. This study recommended BSE for university students for early detection of breast cancer.